Concepções de Desenvolvimento Infantil e Estilos Comunicativos nas Interações Educador-Criança - Santos, Ellis Regina Ferreira dos (2012)
In this study, starting from the vygotskian presuppositions, together with the Perspective of Social Interaction of the Language Scholars, we aim to investigate the conceptions of educators about the child development and to analyze the educator-children interaction in public and private day care centers. It is a quantitative and qualitative study, having as participants 24 educators and 95 children aged between 24 and 30 months accompanied by them. The tools used were: a socio-demographic questionnaire; semi-structured interview; observation, through filming, of the educator-child polyadic interactions, prioritizing the register of communicative styles of educators and the child communicative behaviors. The data analysis occurred in the following way: for the material collected with the questionnaires, a survey was carried out about the frequency of the socio-demographic data of the participants; the semi-structured interviews were analyzed through the analysis of the thematic category content; for the transcriptions of the observations of the interactions filmed and the survey of the frequency of the interaction categories, in the first case, it was used the operational norms of the CHAT (Codes for the Human Analysis of Transcripts) and, in the second case, the CLAN (Computerized Language Analysis), both being components of the computational program CHILDES (Child Language Data Exchange System). In addition to that, the Chi-square Statistical Test was used to identify the existence of significant differences between the frequencies of categories and the sub-categories of the two groups of educators. It was verified that, in relation to the concepts about child development, there was a predominance of the Development by stages sub-category in both groups of educators. These female educators pointed out the unstructured socio-familiar Setting and the Educator s lack of qualification as the main unfavorable aspect to the promotion of child development and characterized the development of children when inserted in the routine of the day care centers as being positive, still existing a certain consensus between them about the Strategies used for promoting the development of children. It was also verified that the educators of public day care centers regarded as being the Educator s role mainly to Educate children; the educators of private day care centers, on the contrary, emphasized to Stimulate the child development. In relation to communicative Styles of educators, the prevalence of Requisitions was observed in both groups of educators, especially in those of Requisitions of general response and those of Requisitions of specific response. Also the Assertions and Directives of attention between the educators of public day care centers and private ones, the Directives of attention being more frequent in private day care centers. In relation to the analysis of child communicative Behaviors, the verbal language prevailed in comparison with the non-verbal in both groups of children, and these results converge with the discourse of the educators of both groups of day care centers, since it prioritized the use of strategies to stimulate the development of the children‟s speech, such as to tell and retell the story and to sing. Thus, it is hoped, that this research will contribute for the studies that are already being carried out in the area and with the planning of interventions and future public policies related to educative practice of the day care center‟s educator in the context of interactions with the child.